Filets Sociaux (Jigisémèjiri) program midline report - Hidrobo, Melissa; Roy, Shalini; Huybregts, Lieven; Njee-Bugha, Leila; Sessou, Eric; Kameli, Yves (International Food Policy Research Institute, 2019)
This report presents findings from the impact evaluation of the Jigisémèjiri program at midline. It first provides background on the evaluation, including details on the program and interventions. It then relates first-order, second-order, and third-order outcomes of interest in a conceptual framework, which guides our analysis and structures the report. The report next describes the evaluation design, sampling, and data collection process. It then presents statistics on beneficiaries’ experience with the CTs and AM. Last, it uses the baseline and midline data, exploiting the randomized design, to estimate the impacts of the program on its beneficiary population at midline, distinguishing between household-level outcomes and child-level outcomes. Given that the baseline report showed that the randomization process was successful at creating similar groups for comparison for the impact evaluation with similar preprogram characteristics, the impacts at midline can be interpreted as truly caused by the program rather than simply correlated with its receipt.